Surgical Techniques for the Treatment of Temporal Lobe Epilepsy. (22nd March 2012) - Al-Otaibi, Faisal; Baeesa, Saleh S.; Parrent, Andrew G.; Girvin, John P.; Steven, David
Abstract : Temporal lobe epilepsy (TLE) is the most common form of medically intractable epilepsy. Advances in electrophysiology and neuroimaging have led to a more precise localization of the epileptogenic zone within the temporal lobe. Resective surgery is the most effective treatment for TLE. Despite the variability in surgical techniques and in the extent of resection, the overall outcomes of different TLE surgeries are similar. Here, we review different surgical interventions for the management of TLE.